Travestissement burlesque et parodie du roman africain dans Les écailles du ciel de Tierno Monénembo - Gacoin-Marks, Florence (Vestnik za tuje jezike, 2012)
The paper deals with The scales of the sky, a novel by the Guinean writer Tierno Monénembo. The analysis shows that we can consider this novel as a comical synthesis of previous African novels, especially of novels about recent Guinean history. The conclusion of the paper is that this synthesis is achieved by using two different comical literary genres: burlesque and parody.
Keywords: Monénembo, Tierno, 1947-; "Les écailles du ciel"; afriški roman; gvinejska književnost; frankofonske književnosti; parodija; burleskna travestija